Effect of phosphorus and detasseling on yield of babycorn (Zea mays) - SAHOO, S C; PANDA, M M (The Indian Journal of Agricultural Sciences, 2014)
Field experiments were conducted during winter seasons of 1997-98 and 1998-99 at Jashipur, Orissa to find out the effect of levels of phosphorus and detasseling on yields of baby corn and green fodder. Babycorn production increased with increase in the levels of phosphorus application up to 26.2 kg/ha beyond which there was no yield advantage. Detasseling increased babycorn production by 7.4%, net profit by 5.7% and benefit: cost ratio by 5.4%.